SPE Annual Technical Conference and Exhibition 1999
DOI: 10.2118/56509-ms
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Electrical Anisotropy of Laminated Reservoirs: A Tensor Resistivity Saturation Model

Abstract: This paper was prepared for presentation at the 1999 SPE Annual Technical Conference and Exhibition held in Houston, Texas, 3–6 October 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Empirical evidence suggests that electrical conductivity of Earth materials is anisotropic as a rule, rather than an exception, and anisotropy is observed on the cm scale [8], the m scale [9] and the km scale [10]. Causes of electrical anisotropy are varied, ranging from preferential direction of rock fractures and layering of rock-strata to the alignment of crystals in the rock matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence suggests that electrical conductivity of Earth materials is anisotropic as a rule, rather than an exception, and anisotropy is observed on the cm scale [8], the m scale [9] and the km scale [10]. Causes of electrical anisotropy are varied, ranging from preferential direction of rock fractures and layering of rock-strata to the alignment of crystals in the rock matrix.…”
Section: Introductionmentioning
confidence: 99%
“…and finely layered anisotropic sands. (i.e., layers of sand of different grain sizes) (Schoen et al, 1999). Gernez et al (2019) confirmed a strong link between K and electrical resistivity anisotropies using hydraulic tomography and Electrical Resistivity Tomography (ERT) in Saint-Lambert-de-Lauzon, Canada.…”
mentioning
confidence: 66%
“…The micro genesis of low resistivity oil layers is complex and diverse, generally caused by a combination of one or more factors such as reservoir lithology, physical properties, and oil bearing properties. The micro genesis is not entirely the same under different sedimentary backgrounds (Zheng et al, 2018;Wang et al, 2016;Liao et al, 2010;Schoen et al, 1999). The reason why rocks exhibit low resistivity is mainly due to the particularity of rocks and fluids, and their electrical conductivity is mainly affected by both fluid and rock skeleton.…”
Section: Microgenesis Of Low Resistivity Reservoirsmentioning
confidence: 99%